Penerapan Uji-T Independen untuk Sistem Chatbot Gaotek - Dias Juliansyah; Hannie Hannie; Ade Andri Hendriadi (Syntax Corporation Indonesia, 2024)
Artificial intelligence has become a primary focus in the development of computer systems that mimic human brain functions. One application is the development of Chatbots to assist in various fields. In this context, the research aims to evaluate the effectiveness of two types of Chatbots, namely Chatbot Gemini and ChatGPT, in providing customer service at GAOTek Inc. Through the application of Independent T-tests, the research findings indicate a significant difference in the performance of the two Chatbots. ChatGPT exhibits a lower average score compared to Chatbot Gemini, demonstrating significant efficiency superiority. The Independent T-test statistical results show the rejection of the null hypothesis, indicating a significant difference between the two groups. The alternative hypothesis is accepted, confirming a distinction in the performance of the two Chatbots. Thus, ChatGPT is declared as the most efficient Chatbot in the context of customer service at GAOTek Inc. These results are expected to provide valuable insights for the development and implementation of Chatbots in enhancing customer service effectiveness across various industries, particularly at GAOTek Inc.